Acute Bacterial Meningitis and Systemic Abscesses due to Streptococcus dysgalactiae subsp. equisimilis Infection - M. Jourani; T. Duprez; V. Roelants; H. Rodriguez-Villalobos; P. Hantson (Case Reports in Infectious Diseases)
Disseminated abscesses due to group G β-hemolytic Streptococcus dysgalactiae were observed in a 57-year-old cirrhotic patient with the skin being the putative way of entry for the pathogen. S. dysgalactiae is a rare agent in human infections responsible for acute pyogenic meningitis. The mortality rate associated with S. dysgalactiae bacteraemia and meningitis may be as high as 50%, particularly in the presence of endocarditis or brain abscesses. In our patient, main sites of infections were meningitis and ventriculitis, spondylodiscitis, septic arthritis, and soft-tissue infections. In contrast, no endocarditis was evidenced. Cirrhosis-related immune suppression was considered as a pathophysiological cofactor for the condition. Fortunately, clinical status improved after long-term (3 months) antimicrobial therapy.